2022
DOI: 10.3390/su14052569
|View full text |Cite
|
Sign up to set email alerts
|

The Wine Effects in Tourism Studies: Mapping the Research Referents

Abstract: This research provides an empirical overview of articles and authors referring to research on wine tourism, analyzed from 2000 to 2021, and what they contribute to deepening the Sustainable Development Goals (SDGs) 8. The articles were examined through a bibliometric approach based on data from 199 records stored in the Web of Science (JCR), applying traditional bibliometric laws, and using VOSviewer for data processing and metadata. The results highlight an exponential increase in scientific production withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 93 publications
2
9
0
Order By: Relevance
“…A significant number of papers were published between 2018 and 2021 (57.14%). This finding aligns with Campos-Andaur et al (2022), Nave et al (2021) and Triantafyllou et al (2020), who reported increased scientific production in wine tourism. The most relevant journals in the area of wine tourism experiences are ranked using Bradford’s Law of Scattering (Table 1), which describes the distribution of literature across journals (Vickery, 1948).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…A significant number of papers were published between 2018 and 2021 (57.14%). This finding aligns with Campos-Andaur et al (2022), Nave et al (2021) and Triantafyllou et al (2020), who reported increased scientific production in wine tourism. The most relevant journals in the area of wine tourism experiences are ranked using Bradford’s Law of Scattering (Table 1), which describes the distribution of literature across journals (Vickery, 1948).…”
Section: Resultssupporting
confidence: 90%
“…Survey-based empirical studies appear to be a widely adopted research method to describe and measure wine tourism experiences. This finding aligns with Campos-Andaur et al (2022), Nave et al (2021) and Weatherbee et al (2019). It was also observed that netnographic studies in wine tourism experiences through social media posts had gained popularity among scholars.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…However, these reviews, including some bibliometric analyses, tend to focus on specific journals (Weatherbee et al , 2019) or themes, e.g. the determinants of wine preferences and willingness to pay at multiple levels of analysis (Carollo et al , 2022; Schäufele and Hamm, 2017), consumer behaviour (Lockshin and Corsi, 2012), wine tourism (Campos-Andaur et al , 2022; Durán-Sánchez et al , 2016; Gómez et al , 2018; Kotur, 2023; Sánchez et al , 2017; Santos et al , 2019), sustainability in the wine industry (Barbosa et al , 2018; Santini et al , 2013), climate change effects and adaptation strategies (Sacchelli et al , 2016), environmental concerns in wine production (Christ and Burritt, 2013), life cycle assessment literature (Casolani et al , 2022) and pesticide use in vineyards (Regus et al , 2022).…”
Section: Introductionmentioning
confidence: 99%